(untitled) (Research, Society and Development, 2020)
This study aims to identify the guidelines provided by the nurse to the pregnant woman during prenatal care and to describe the influence of these guidelines in the construction of knowledge of the pregnant woman with Perinatal Hemolytic Disease. This is an integrative review conducted in the Virtual Health Library database, where data from LILACS, SciELO and Bdenf are available. Were included 03 publications between 2011 and 2018 in the category Importance of the education of clients and health professionals in the care of Perinatal Hemolytic Disease. We have noticed that there is a vast lack of access to information relevant to prenatal care and about the pathology in question. In view of this, the study rescues the significance of a high-risk prenatal care performed concomitantly by the medical professional and the nurse, since the nurse, as an educator, can be a key element in the process of remodeling care.